PENENTUAN MASA KADALUWARSA RENGGINANG DENGAN MENGGUNAKAN MODEL LABUZA - Anom S. Wijaya, I Made; Ayu Nocianitri, Komang; Anugrah, Anton (Agrotekno, 2012)
The objective of this research was to determine the shelf life of the traditional snack food “rengginang” using the Labuza Model (the accelerated storage studies method (ASS Method)), as well as comparing the results with the extended storage studies (ESS) method. The rengginang was packed with the polyethelene plastic 0.03 mm, and store at room temperature with 75% of RH. The shelf life was determine using the accelerated storage studies method with Labuza Model, and extended storage studies method. The parameters observe in determination of shelf life were initial moisture content, critical moisture content, equilibrium moisture content, slope of sorption isotherm curve, moisture permeability of plastic used, ratio of plastic package are and product weight, and saturated pressure of storage condition. The result showed that the shelf life of rengginang calculated using Labuza Model (ASS Method) was 39 days, while the ESS method resulted 46 days. These was indicating that the Labuza model can be used to predicting the shelf life of rengginang like snack food.
Keywords: shelf life, ASS methods, ESS methods, rengginang